Postoperative outcomes associated with surgical care for women in Africa: an international risk-adjusted analysis of prospective observational cohorts - Paterson, A; Maswime, S; Hardy, A; Pearse, RM; Biccard, BM (Elsevier, 2022)
Background: Improving women's health is a critical component of the sustainable development goals. Although obstetric outcomes in Africa have received significant focus, non-obstetric surgical outcomes for women in Africa remain under-examined.